OPTIMALISASI POTENSI TANAMAN PALA SEBAGAI ANTIBAKTERI Escherichia coli MENGGUNAKAN METODE EKSTRAKSI - Tanendri Arrizqiyani; Novy Sonjaya; Ajeng Asty (Universitas Muhammadiyah Semarang, 2017)
People use plants to become traditional medicine to treat various diseases. Fuli and seed of nutmeg (Myristica fragrans) have antimicrobial substances that can lyse cell walls, thus affecting the growth of bacterial cells. The aim of this research is to know the optimum inhibition concentration of extract fuli and seed of nutmeg on growth of Escherichia coli.The method used is maceration to obtain antibacterial active compound from fuli and seed of nutmeg followed by GCMS analysis. Testing of the optimum inhibitory potential of fuli and seed extract was conducted by Kirby Bauer method at concentrations ranging from 5%, 15%, 25%, 35%, 45%, 55%, 65%, 75%, 85%, 95% 85%, 95% and 100%. The results showed that the optimum inhibition concentration of seed extract and mace were 55% and25%. The cause of the inhibition zone zero at concentrations of 65%, 75%, 85%, 95%, 85%,95% and 100% allegedly caused by low speed diffusion of extract to medium. Keywords: Seed and Mace of Myristica fragrans, Escherichia coli